Stress concentration factor prediction by the multi-dimensional Lagrangian interpolation method - Lee, Chi King (2014)
A new approach based on the multi-dimensional Lagrangian interpolation method, which is widely used in the finite element method, is proposed for the prediction of stress concentration factor for tubular joints. When comparing with the parametric regression method, this new method uses the same set of numerical parametric study results as its inputs. The accuracy of the proposed method is validated by applying it to predict the stress concentration factor and hot spot stress of partially overlapped circular hollow section K-joints. Numerical results indicated that the new method is more reliable and accurate than the parametric regression method.